The Patriotic Consensus: Unity, Morale and the Second World War in Winnipeg - Keshen, Jeff (Labour / Le Travail, 2015)
This article reviews the book, "The Patriotic Consensus: Unity, Morale and the Second World War in Winnipeg," by Jody Perrun.